VD_FINDINFO Jug / 2013 / 10 vom 20. Juli 2012 - VD Tribunal cantonal (2012)
ABUS D'AUTORITÉ, PEINE PÉCUNIAIRE, FIXATION DE LA PEINE, LÉSION CORPORELLE SIMPLE | 123 ch. 2 al. 2 CP, 123 ch. 3 CP, 312 CP, 49 al. 1 CP